Energy measurement of 241Am-9Be neutrons by tagged neutron time-of-flight. (March 2023) - Shana, F.S.; Golda, K.S.; Saneesh, N.; Arora, D.; Sugathan, P.
Abstract: Neutron energy spectrum of a 241 Am- 9 Be source was measured in the energy range of 0.3 to ∼ 6.5 MeV using γ -ray tagged neutron time-of-flight method. BC501A type organic liquid scintillator detector was used at a flight path of 175 cm to detect neutrons with good energy resolution. The de-excitation γ -ray emitted in coincidence with neutrons was detected using a fast BaF2 detector. The measured data has been compared with the ISO 8529-2 standard neutron reference spectrum and found good agreement in the overlapping energy region. Present measurement applied efficiency correction to the data and extended up to 0.3 MeV in the lower energy region compared to earlier reported measurement using similar technique. Highlights: 241 Am 9 Be neutron source is used for detector characterization and calibration. Neutron energy was measured using tagged neutron Time-of-flight method. Energy of neutrons from Am-Be source was measured from 0.3 MeV to 6.5 MeV. Measured neutron energy spectrum matches with ISO standard data.